Group techniques that teachers use in the teaching-learning process to achieve and integrated significant learning in english learners. - Sarango Gonza, Manuel Iván (Machala : Universidad Técnica de Machala, 2015)
El objetivo general del presente trabajo identificar las técnicas grupales que los docentes utilizan para lograr un aprendizaje significativo integrado en los estudiantes de inglés. Al hablar de técnicas grupales decimos que son recursos metodológicos que el docente desarrolla en el aula mediante la planificación consecutiva de un conjunto de tareas con la finalidad de llevar a cabo procesos de enseñanza-aprendizaje, en los que los individuos forman parte activa del proceso.
The general objective of this study identifies the group techniques that teachers use to get an integrated significant learning in the English students. To talk of group techniques, we say they are methodological resource that the teacher develop in the classroom through the straight planning of a task group with the objective to do teaching-learning process, where the gay is active part of the process.
Keywords: TECHNIQUE; TEACHER; TEACHING-LEARNING; PROCESS